Sleep Disorders and Atrial Fibrillation: Current Situation and Future Directions: - Sepehri Shamloo, Alireza; Arya, Arash; Dagres, Nikolas; Hindricks, Gerhard (Galen Medical Journal, 2018)
Atrial fibrillation (AF) is a growing health problem worldwide. In recent years, there has been a rising interest in the relationship between sleep disorders and AF. Several studies have reported higher prevalence and incidence rates of AF in patients with obstructive sleep apnea-hypopnea syndrome (OSAHS). However, some believe that OSAHS is not a risk factor for AF; but AF, by itself, is regarded as one of the possible triggers for OSAHS. In this study, the related literature investigating the association between OSAHS and AF was reviewed, and then the possible mechanisms of this interplay were discussed. To conclude, recommendations for further research in this field were presented to researchers and some points were highlighted for physicians.[GMJ.2018;7:e1416]